Complications with the Zurich Canine Total Hip Replacement System in an Initial Series of Cases Performed by a Single Surgeon - Franklin, Samuel P.; Miller, Nathan A.; Riecks, Todd (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to quantify the complications using the Zurich total hip replacement system in an initial series of cases performed by a single surgeon who had experience with other total hip replacement systems.Materials and Methods This was a retrospective study in which complications were classified as major if any treatment was needed or if the outcome was less than near-normal function. Complications that did not warrant treatment and that did not result in function that was inferior to near-normal were considered minor. Outcomes were assessed by radiographic review, physical examination, subjective gait evaluation or, in one case, by objective gait analysis. Bilateral total hip replacements were considered separate procedures.Results The first 21 procedures in 19 dogs performed by a single surgeon were included. The mean time to follow-up was 48 weeks (range: 8–120 weeks; standard deviation: 36 weeks). Two cases (of 21) experienced major complications including one dog with excess internal femoral rotation during weight bearing and one dog having luxation. One case (of 21) had a minor complication; femoral fracture in the presence of an intact bone plate that maintained alignment and healed without treatment.Clinical Significance A high rate of successful outcomes with few major complications can be obtained in the initial cases treated using the Zurich total hip replacement system for surgeons with prior experience with other total hip replacement systems.
Keywords: total hip replacement; total hip arthroplasty; total joint replacement; dog; complications